The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s00455-022-10502-9
|View full text |Cite
|
Sign up to set email alerts
|

Position Statement of the Union of European Phoniatricians (UEP): Fees and Phoniatricians’ Role in Multidisciplinary and Multiprofessional Dysphagia Management Team

Abstract: The need for multidisciplinary and multiprofessional management of dysphagia is constantly increasing and creating a major challenge for healthcare professionals and society, especially in terms of professional expertise and human resources. The distribution of tasks among the dysphagia team members, which includes phoniatricians, otolaryngologists, and speech-language therapists, is flexible and overlapping. For assessing dysphagia, the (fibreoptic) flexible endoscopic evaluation of swallowing (FEES), with or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…A multidisciplinary, multiprofessional dysphagia team includes pediatricians, pediatric neurologists, pediatric intensivists, otorhinolaryngologists, speech–language pathologists, phoniatricians, pediatric pulmonologists, pediatric surgeons, pediatric gastroenterologists, nutrition specialists, and rehabilitation specialists, who provide coordinated and integrated care with continuity through care transitions. Within the pediatric dysphagia team, the allocation and distribution of tasks are varied and dynamic, determined by different professional developments of medical and healthcare disciplines in different countries and the relevant legal regulations [ 7 , 8 , 22 ]. A collaborative approach to the FEES examination by an otolaryngologist and a speech–language pathologist facilitates the examination and fosters best practices in managing pediatric dysphagia.…”
Section: The Pediatric Dysphagia Teamsmentioning
confidence: 99%
See 2 more Smart Citations
“…A multidisciplinary, multiprofessional dysphagia team includes pediatricians, pediatric neurologists, pediatric intensivists, otorhinolaryngologists, speech–language pathologists, phoniatricians, pediatric pulmonologists, pediatric surgeons, pediatric gastroenterologists, nutrition specialists, and rehabilitation specialists, who provide coordinated and integrated care with continuity through care transitions. Within the pediatric dysphagia team, the allocation and distribution of tasks are varied and dynamic, determined by different professional developments of medical and healthcare disciplines in different countries and the relevant legal regulations [ 7 , 8 , 22 ]. A collaborative approach to the FEES examination by an otolaryngologist and a speech–language pathologist facilitates the examination and fosters best practices in managing pediatric dysphagia.…”
Section: The Pediatric Dysphagia Teamsmentioning
confidence: 99%
“…A collaborative approach to the FEES examination by an otolaryngologist and a speech–language pathologist facilitates the examination and fosters best practices in managing pediatric dysphagia. Due to varying national practices and legislation, it is difficult to define generally accepted recommendations [ 22 ]. FEES training opportunities are widely available.…”
Section: The Pediatric Dysphagia Teamsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many healthcare professionals and patients with dysphagia are unaware that dysphagia is treatable [11]. Professionals responsible for the delivery of dysphagia rehabilitation interventions mostly consist of speech and language therapists [12]. Recent studies developed various approaches and procedures for dysphagia such as electrical stimulation therapy, which is widely used as a facilitative rehabilitation strategy to improve dysphagia [13].…”
Section: Introductionmentioning
confidence: 99%
“…Limited awareness, and inadequate knowledge are some of the reasons that were attributed to limited screening for PED in the intensive care units (ICUs) [20]. Additionally, although a speech and language pathologist/ therapist (SLP/SLT) is helpful in the evaluation and management of dysphagia [21], dysphagia is a complex problem that requires multi-professional targeted approach [22,23]. Moreover, little evidence showed that assessment and management of dysphagia are conducted by nurses and non-specialists in ICUs [24].…”
Section: Introductionmentioning
confidence: 99%